Factors affecting office rent in Kuala Lumpur (KL) - Cheah, Jun Hwa; Ng, Siew Imm; Teoh, Kenny Guan Cheng; Lee, Chin (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
The oversupply of office space in the Golden Triangle Kuala Lumpur (GTKL) and slow on-going demand has resulted in pressure on rental performance. Studies have shown that there are several strategies to improve rent performance. The purpose of this paper is to obtain a deeper understanding of these strategies and their applicability in the context of GTKL. Questionnaires were distributed to 42 office buildings in the GTKL. A total of 212 tenants completed the questionnaire and secondary data on building certifications and the building average rents were extracted from reliable property website sources. The results suggest that office building rental performance can be improved if the building management charges lower rent to longer-stay tenants, attracts more foreign-owned or bigger-sized firm and gets Multimedia Super Corridor (MSC) or Green certifications. The implications for managers and theories in this regard are then discussed.